Natural Compounds Derived from Camellia sinensis as Therapeutic Agent to Treat Non-Small Cell Lung Carcinoma (NSCLC): A Molecular Docking Study - Haidar Ali Hamzah; Putri Mahirah Afladhanti; Muhammad Despriansyah Romadhan (Sriwijaya Journal of Medicine, 2022)
Cancer is one of the biggest health problems with lung cancer as the first rank in the number of new cases and deaths. Non-small cell lung carcinoma (NSCLC) is a type of lung cancer which accounts for about 85% cases. Previous research identified the role of epidermal growth factor receptor (EGFR) as the most suitable target to treat NSCLC. This study used a molecular docking technique to identify the potential compounds derived from Camellia sinensis (green tea) leaves as therapeutic agent to treat NSCLC. We tested 12 compounds in green tea leaves along with gefitinib as a comparative drug. Docking was carried out on EGFR as receptor target by Autodock Tools and Autodock Vina. Molecular interactions were visualized by Discovery Studio v16. All compounds met the criteria as drugs based on Lipinski’s solubility test and were safe to use based on toxicity test with AdmetSAR. Docking results showed that all compounds had affinity to EGFR receptor. Catechin and myricetin had the same energy bonds as gefitinib which were -7,9 kcal/mol, while theaflavin gallate, theaflavin digallate, epicatechin gallate, epigallocatechin-3-gallate, catechin gallate, thearubigin, quercetin, and kaempferol were proven to have the strongest binding energy compared to gefitinib which were -10.6, -9.8, -8.9, -8.9, -8.5, -8.3, -8.0, and -8.0 kcal/mol, respectively. All compounds have the potential for development into drugs for NSCLC treatment. Further in vitro and in vivo investigations are needed to bring these compounds to the clinical setting.